Business Ethics Teaching for Effective Learning - Sims, Ronald R. (2002)
This paper is concerned with answering thequestion: ``How can business ethics be taught tostudents so that effective learning takesplace?'' It is the contention of this paperthat the question is best answered by focusingon six areas important to teaching businessethics: goals, relevancy, experientialpedagogy, classroom climate, debriefing, andoutcomes assessment.
Keywords: relevancy; Goals; Experiential Learning; debriefing; classroom climate; Business Ethics; Assessment